Studi Deskriptif Kompetensi Kepribadian Konselor yang Diharapkan Siswa - Fatmawijaya, Heru Andrian (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2015)
This study aims to explore the high qualified counselorsâ personal competence at SMA Negeri 11 Yogyakarta. This research is a descriptive research. The participants of this research were 169 students consisting of class X, XI and XII class selected by simple random sampling. The instrument for the data collection is questionnaires of counselorsâ personal competence. There are four aspects that were outlined in the questionnaires namely, godly and devoted to the Almighty God, respect and uphold the values of humanity, individualist and independent, having integrity and stability of a strong personality, having high performance quality. The data analysis techniques used a simple calculation in which grouping the data into three criterias, they are, poor, moderate, and good. The results showed that the expected counselorsâ personal competence at SMA Negeri 11 Yogyakarta reaching the score of each are 50.3% in good criteria, 49.7% in moderate citeria and 0% in poor criteria.The results of this study can be used as the basis for the development of counselorsâ personal competence in order to become high qualifeid counselors as expected by the students. The counselors who have a strong personality as the expected by students can improve students enthusiasm to acquire the guidance and counseling services at schools.